Dietary Cholesterol Impairs Memory and Memory Increases Brain Cholesterol and Sulfatide Levels. - Darwish, Deya S.; Wang, Desheng; Konat, Gregory W. (Behavioral Neuroscience, 2010)
Cholesterol and sulfatides play many important roles in learning and memory. To date, our observations about the effects of cholesterol on learning have been assessed during response acquisition: that is, the learning of a new memory. Here, we report for the first time to our knowledge, on the effect of a cholesterol diet on a previously formed memory. Rabbits were given trace conditioning of the nictitating membrane response for 10 days, then fed a 2% cholesterol diet for 8 weeks, and then assessed for memory recall of the initially learned task. We show that dietary cholesterol had an adverse effect on memory recall. Second, we investigated whether dietary cholesterol caused an increase in brain cholesterol and sulfatide levels in four major brain structures (hippocampus, frontal lobe, brainstem, and cerebellum) using a technique for analyzing myelin and myelin-free fractions separately. Although our data confirm previous findings that dietary cholesterol does not directly affect cholesterol and establish that it does not affect sulfatide levels in the brain, these levels did increase rather significantly in the hippocampus and frontal lobe as a function of learning and memory. Reprinted by permission of the publisher.